Impact of external assurance on corporate climate change disclosures: new evidence from Finland - Dutta, Probal; Dutta, Anupam (Journal of applied accounting research, 2021)
PurposeThe purpose of this research is to examine the impact of external assurance on the level of voluntary corporate climate change disclosures by Finnish firms.Design/methodology/approachThe sample of this study includes 228 firm-year observations over the period 2008–2015 for listed Finnish companies that have issued sustainability reports and responded to the Carbon Disclosure Project (CDP) questionnaire at least once during the sample period. The authors conduct a panel regression analysis to study the afore-mentioned linkage. In addition, the Tobit regression model is also estimated to check the robustness of our findings.FindingsThe findings suggest that assurance has a highly significant positive impact on the level of corporate climate change disclosures even after controlling for the effect of a number of control variables. Moreover, among the control variables, firm size and asset age are found to have significant effect on the extent of carbon emissions disclosure. Furthermore, the additional analysis reveals that the type of assurance providers (accounting firms vs non-accounting firms) and the type of financial auditors (Big4 financial auditors vs non-Big4 financial auditors) do not influence the level of climate change disclosure of assured companies.Research limitations/implicationsThis research is subject to certain limitations. First, the source of the data used in this research is the CDP database which has limitations in that it is a voluntary disclosure process where all the observations collected are self-reported by the responding firms. This may bias the reported findings. Second, our sample includes only listed companies and hence the results might have limited explanatory capacity for unlisted firms.Practical implicationsBy using the results of this research, corporate managers will be able to reduce the information asymmetry between various stakeholders and them through disclosure of accurate, reliable and credible environmental information. Such disclosures will, in turn, allow socially responsible investors to choose eco-friendly investments and will thus enable them to make appropriate investment decisions.Originality/valueResearch on the external assurance-corporate climate change disclosure nexus is scarce. This study addresses this gap in the nonfinancial disclosure assurance literature by demonstrating that external assurance increases the level of voluntary corporate climate change disclosure. Drawing on stakeholder-agency theory, this study views external assurance as a monitoring structure that potentially curbs the monitoring problem between corporate managers and other stakeholders and increases the amount of climate change disclosures making a possible avenue for the reduction of the information asymmetry between them.